A comparison of integrated and designated ELD models on second and third graders' oral English language proficiency. Issue 3 (21st April 2022) - Edelman, Emily R.; Amirazizi, Samira A.; Feinberg, Daniel K.; Quirk, Matthew; Scheller, Jennifer; Pagán, Carlos R.; Persoon, Jamie
Abstract : This article reports on a longitudinal, quasi‐experimental comparison of two English language development (ELD) models implemented from kindergarten through Grade 3 to support oral English language development among Spanish‐speaking English language learners (ELLs). Specifically, the study examined oral English language proficiency among students who received only integrated English language development (I‐ELD; n = 39) and students who received I‐ELD with 30 minutes of daily designated ELD (D‐ELD) entailing four specific routines and strategies (n = 65). The study also compared oral proficiency with English‐only speakers (EO) from the same school (n = 47). Oral language proficiency was measured by the IDEA Proficiency Test (IPT I‐Oral; Ballard & Tighe, 2017). A repeated‐measures analysis of variance (ANOVA) across Grades 2 and 3 indicated significant (p < .001; η2 = 0.53) increases in oral proficiency for ELL students who received D‐ELD. A follow‐up analysis of covariance (ANCOVA) indicated significant positive effects (p < .001; η2 = 0.19) of the D‐ELD approach on ELL students' oral proficiency compared to only I‐ELD in Grade 3. The ANCOVA also found no significant (p > .05) differences in oral proficiency between ELL students who received D‐ELD and EO students in Grade 3, indicating similar oral English skills. The D‐ELD model's instructional strategies and practical implications are discussed.